Data License Workshop for Information Management and Communications teams - from CCAFS to CIAT-All - Roa, Carolina (2019)
As CCFAS/CGIAR follows an open access policy and FAIR principles, you are likely to upload curated data, analyzed data in an institutional repository with all the metadata and add the Open Access logo. But it is saying “Open Access” a self- explanatory concept that lets users know how they can use the data? If not, what else would we need to add? What parameters should we take into account to add or decide upon terms?